Clinical Value of High Mobility Group Box 1 and the Receptor for Advanced Glycation Endproducts in Head and Neck Cancer: A Systematic Review - Nguyen,Austin (2016)
Abstract Introduction High mobility group box 1 is a versatile protein involved in gene transcription, extracellular signaling, and response to inflammation. Extracellularly, high mobility group box 1 binds to several receptors, notably the receptor for advanced glycation end-products. Expression of high mobility group box 1 and the receptor for advanced glycation end-products has been described in many cancers. Objectives To systematically review the available literature using PubMed and Web of Science to evaluate the clinical value of high mobility group box 1 and the receptor for advanced glycation end-products in head and neck squamous cell carcinomas. Data synthesis A total of eleven studies were included in this review. High mobility group box 1 overexpression is associated with poor prognosis and many clinical and pathological characteristics of head and neck squamous cell carcinomas patients. Additionally, the receptor for advanced glycation end-products demonstrates potential value as a clinical indicator of tumor angiogenesis and advanced staging. In diagnosis, high mobility group box 1 demonstrates low sensitivity. Conclusion High mobility group box 1 and the receptor for advanced glycation endproducts are associated with clinical and pathological characteristics of head and neck squamous cell carcinomas. Further investigation of the prognostic and diagnostic value of these molecules is warranted.